Household Accounting In Islamic Perspective - Munir Is’adi; Nur Ika Mauliyah (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2023)
This study aims to determine (1) accounting principles in Islam that can be integrated into household financial management (2) obstacles faced by Muslim families in applying sharia accounting in household financial management (3) efforts to improve financial management of household accounting in an Islamic perspective. The method used is phenomenological. The informants in this study were selected through a purposive sampling technique, with the criteria being working and non-working mothers who live in Jember district, East Java province. The results of the study show that (1) accounting principles in Islam that can be integrated into household financial management are taqwa, fairness, transparency, being conservative, avoiding usury, not delaying debt payments, and giving alms (2) the obstacles faced by Muslim families in applying sharia accounting in household financial management include lack of understanding and awareness, implementation challenges, social and economic context, and lack of resources and financial literacy (3) efforts to improve financial management of household accounting in an Islamic perspective are understanding the principles of Islamic finance, using sharia accounting, making sharia-based budgets , and attend Islamic finance education. sharia, create sharia-based budgets, and attend sharia finance education.